Културната историја како предуслов за повеќенасочно историско паметење - Tasevska Hadji Boshkova, Iskra (Сојуз на друштвата за македонски јазик и литература, 2012)
Cultural history (and, concerning the chronology, especially new cultural history) is a domain which acquires unavoidable interdisciplinary accounts and results. Visualizing the wide context between culture-text-history, cultural history enables the reading through, and the reinterpretation of the dominant structures. Cultural history enriches cultural studies with its creativity and modification, thus demonstrating the power of formal argument as vibrating field of tradition, itself realized as a phenomenon (civilization), and as a deep structure (culture). At the same time, this is the main concept, paradigmatic as far as its methods and assumptions of the scientific problems are concerned, which only appear to be illogical or tautological in their connection with the hypothesis.
Keywords: cultural history, reader-response criticism, historic knowledge, Macedonian cultural history, Gane Todorovski